PENINGKATAN KETERSEDIAAN DAN SERAPAN NPK SERTA HASIL TANAMAN JAGUNG BISI-16 MELALUI INOKULASI MIKORIZA DAN PUPUK NPK PADA ALFISOL - Yovita Yasintha Bolly (Agriculture Faculty of Flores University, 2012)
This study is to investigate the influence of mycorrhiza isolates with different origin rhizosphere and fertilizer NPK with different dosage to the availability and absorption of NPK as well as the corn yield and to determine the optimum dosage of fertilizer NPK in each mycorrhiza isolate with different origin rhizosphere and availability and uptake of NPK and corn yields and to determine the optimum dosage of fertilizer NPK for each different origin rhizosphere of isolates mycorrhizal inoculated against corn yield. This study used complete Randomized Block Design (CRBD) consisting of 20 treatment combinations with three replications, they are without mycorrhiza and without fertilizer (m0p0) without mycorrhiza + 25% dose of NPK (m0p1) without mycorrhiza + 50% dose of NPK (m0p2) without mycorrhiza + 75% dose of NPK (m1p3) without mycorrhiza + 100% dose of NPK (m1p4), origin rhizosphere mycorrhiza of the of corn plants + 100% dose of NPK (m2p2) without fertilizer (m1p0) mycorrhiza origin of the rhizosphere of corn plants+ 25% dose of NPK (m1p1) mycorrhiza origin rhizosphere of plants corn + 50% dose of NPK (m1p2) origin rhizosphereof mycorrhiza the corn plants+ 75% dose of NPK (m1p3), mycorrhiza origin of the rhizosphere of corn plants+ 100% dose of NPK (m1p4), origin rhizosphere of mycorrhiza the cassava + without fertilizers ( m2p0), origin of mycorrhiza of the cassava + 25% dose of NPK (m2p1), origin rhizosphere of mycorrhiza of cassava + 50% dose of NPK (m2p2), origin rhizosphere of mycorrhiza of cassava + 75% dose of NPK (m2p3), origin rhizosphere of mycorrhiza of cassava + 100% dose of NPK (m2p4) mycorrhizal from serpong + without fertilizer (m3p0), mycorrhiza from serpong + 25% dose of NPK (m3p1), mycorrhiza from serpong + 50% dose of NPK (m3p2), mycorrhiza from serpong + 75% dose of NPK (m3p3), mycorrhiza from serpong + 100% dose of NPK (m3p4). The results showed that mycorrhiza treatment and dosage of fertilizer NPK can increase the availability of NPK, NPK uptake, dry weight of plant and dry weight of seed. Regression test showed the optimum dosage of NPK on m0 treatment cannot be determined because it is linear, while the optimum dosage of NPK fertilizer on the treatment of inoculated mycorrhizal of origin rhizosphere of corn (m1) is 50.66% the recommended dose, in the treatment of native mycorrhiza rhizosphere of cassava (m2 ) is 45.11%, and the treatment of mycorrhiza from serpong (m3) is 46.10%.